2002
DOI: 10.1002/rcm.666
|View full text |Cite
|
Sign up to set email alerts
|

Micro‐high‐performance liquid chromatography/Fourier transform mass spectrometry with electron‐capture dissociation for the analysis of protein enzymatic digests

Abstract: Electron-capture dissociation (ECD) Fourier transform mass spectrometry (FTMS) employed to generate comprehensive sequence information for the chromatographic analysis of enzymatic protein digests is described. A pepsin digest of cytochrome c was separated by reversed-phase micro-high-performance liquid chromatography (microHPLC) and ionized 'on-line' by electrospray ionization (ESI). The ions thus formed were transferred to and trapped in the FTMS analyzer cell. Typically, no precursor ion isolation was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 21 publications
1
25
0
Order By: Relevance
“…The current ECD protocol remains tedious and time-consuming. The low dutycycle has imposed additional constraints on the implementation of the ECD technique for use in on-line liquid chromatography MS/MS analysis [17,18]. To improve the duty-cycle, Zubarev and co-workers have replaced the heated filament with an indirectly heated dispenser cathode [19].…”
mentioning
confidence: 99%
“…The current ECD protocol remains tedious and time-consuming. The low dutycycle has imposed additional constraints on the implementation of the ECD technique for use in on-line liquid chromatography MS/MS analysis [17,18]. To improve the duty-cycle, Zubarev and co-workers have replaced the heated filament with an indirectly heated dispenser cathode [19].…”
mentioning
confidence: 99%
“…The problem was addressed by the introduction of the heated dispenser cathode by Tsybin in 2001 [113]. The timescale for ECD was reduced significantly (ms) and it became possible to couple ECD with online liquid chromatography [114][115][116]. Palmblad et al [115] coupled LC with ECD for the analysis of a tryptic digest of bovine serum albumin and Davidson and Frego [114] demonstrated LC-ECD analysis of a pepsin digest of cytochrome c. Zubarev and co-workers demonstrated an approach on a modified LTQ FT hybrid linear ion trap FTICR in which a low resolution survey scan in the ion trap was followed by analysis of CID and ECD in the ICR cell [117].…”
Section: Ie Formation Of [M+(n-1)h]mentioning
confidence: 99%
“…The timescale for ECD was reduced significantly (ms) and it became possible to couple ECD with online liquid chromatography [114][115][116]. Palmblad et al [115] coupled LC with ECD for the analysis of a tryptic digest of bovine serum albumin and Davidson and Frego [114] demonstrated LC-ECD analysis of a pepsin digest of cytochrome c. Zubarev and co-workers demonstrated an approach on a modified LTQ FT hybrid linear ion trap FTICR in which a low resolution survey scan in the ion trap was followed by analysis of CID and ECD in the ICR cell [117]. Creese and Cooper [118] undertook a direct comparison of LC-ECD-MS/MS with LC-CID-MS/MS revealed that, CID resulted in greater overall protein coverage, whereas ECD gave higher confidence in peptide sequence, thus showing the complementary nature of CID and ECD for bottom-up proteomics.…”
Section: Ie Formation Of [M+(n-1)h]mentioning
confidence: 99%
“…As a consequence, the electron irradiation time required exceeded several seconds and tens of seconds, with some exceptions. 28,58 The novel electron-injection systems based on indirectly heated cathodes provided increased electron flux, larger overlap of ion and electron clouds and better control of the electron energy. As a result, the reliability of ECD was improved and the reaction rate was increased by about two orders of magnitude.…”
Section: Electron Capture Dissociation Ratementioning
confidence: 99%